Markers predicting critical illness and mortality in COVID-19 patients: A multi-centre retrospective study - Büyükaydın, Banu; Karaaslan, Tahsin; KARATOPRAK, CUMALİ; Karatoprak, Cumali; Karaaslan, Esra; Sasak Kuzgun, Gulsah; Gündüz, Mehmet; ŞEKERCİ, ABDÜSSELAM; Şekerci, Abdusselam; BÜYÜKAYDIN, BANU; Alişir Ecder, Sabahat (My University, 2021)
Aim: In this study, we aimed to investigate early predictors of critical illness and mortality in patients with coronavirus disease 2019 (COVID-19) based onclinical, biochemical, radiological, and epidemiological findings.Materials and Methods: This multi-center, retrospective study was conducted in three centers and included a total of 206 confirmed COVID-19 cases usingreverse transcription-polymerase chain reaction (RT-PCR). Data of survivors and non-survivors were compared, and predictors of mortality were examined.Results: Among the patients, 103 (50%) were males with a mean age of 52.8±16.7 years; 88.3% of the patients were discharged in a healthy condition, while11.7% died. The mean age was significantly higher in non-survivors. Dyspnea occurred in 32.5% of patients, and a significant correlation was found betweendyspnea and mortality (p<0.001). Thoracic computed tomography (CT) findings were positive in 88.8% of patients. The most frequent imaging findings wereground-glass opacities in 86.4% and consolidation in 33% of patients. The mortality rate was significantly higher in patients with comorbidities (p<0.001).There was also a significant correlation between lymphocytopenia and mortality (p<0.001). A positive correlation was found between mortality risk andplatelet-to-lymphocyte, neutrophil-to-lymphocyte, and red cell distribution width indices. The mortality risk was significantly higher in patients with acutekidney injury (10.7%) (p<0.001).Discussion: These results suggest that advanced age, coexisting diabetes, hypertension, heart failure, chronic kidney disease, or acute kidney injury are associatedwith an increased mortality risk. The presence of dyspnoea or consolidation on thoracic CT can predict an increased mortality risk in COVID-19 patients.